Thalamic Gap Junctions Control Local Neuronal Synchrony and Influence Macroscopic Oscillation Amplitude during EEG Alpha Rhythms - Hughes, Stuart; Lőrincz, Magor; Turmaine, Mark; Crunelli, Vincenzo (Frontiers in Psychology, 2011)
Although EEG alpha () (8-13 Hz) rhythms are often considered to reflect an ‘idling’ brain state, numerous studies indicate that they are also related to many aspects of perception. Recently, we outlined a potential cellular substrate by which such aspects of perception might be linked to basic  rhythm mechanisms. This scheme relies on a specialized subset of rhythmically bursting thalamocortical (TC) neurons (high-threshold bursting cells) in the lateral geniculate nucleus (LGN) which are interconnected by gap junctions (GJs). By engaging GABAergic interneurons, that in turn inhibit conventional relay-mode TC neurons, these cells can lead to an effective temporal framing of thalamic relay-mode output. Although the role of GJs is pivotal in this scheme, evidence for their involvement in thalamic  rhythms has thus far mainly derived from experiments in in vitro slice preparations. In addition, direct anatomical evidence of neuronal GJs in the LGN is currently lacking. To address the first of these issues we tested the effects of the GJ inhibitors, carbenoxolone (CBX) and 18-glycyrrhetinic acid (18-GA), given directly to the LGN via reverse microdialysis, on spontaneous LGN and EEG  rhythms in behaving cats. We also examined the effect of CBX on  rhythm-related LGN unit activity. Indicative of a role for thalamic GJs in these activities, 18-GA and CBX reversibly suppressed both LGN and EEG  rhythms, with CBX also decreasing neuronal synchrony. To address the second point, we used electron microscopy to obtain definitive ultrastructural evidence for the presence of GJs between neurons in the cat LGN. As interneurons show no phenotypic evidence of GJ coupling (i.e. dye-coupling and spikelets) we conclude that these GJs must belong to TC neurons. The potential significance of these findings for relating macroscopic changes in  rhythms to basic cellular processes is discussed.